Enhanced Charge Transfer and Responsivity in Hybrid Quantum Dot/Graphene Photodetectors Using ZnO as Intermediate Electron‐Collecting Layer. (11th May 2020) - Ahn, Seungbae; Chen, Wenjun; Moreno‐Gonzalez, Miguel A.; Lockett, Malcolm; Wang, Jiaying; Vazquez‐Mena, Oscar
Abstract: Hybrid graphene (Gr)–quantum dot (QD) photodetectors have shown ultrahigh photoresponsivity combining the strong light absorption of QDs with the high mobility of Gr. QDs absorb light and generate photocarriers that are efficiently transported by Gr. Typically, hybrid PbS–QD/graphene photodetectors operate by transferring photogenerated holes from the QDs to Gr while photoelectrons stay in the QDs inducing a photogating mechanism that achieves a responsivity of 6 × 10 7 A W −1 . However, despite such high gain, these systems have poor charge collection with quantum efficiency below 25%. Herein, a ZnO intermediate layer (PbS‐QD/ZnO/Gr) is introduced to improve charge collection by forming an effective p‐n PbS‐ZnO junction driving the electrons to the ZnO layer and then to Gr. This improves the photoresponsivity of the devices by nearly an order of magnitude with respect to devices without ZnO. Charge transfer to Gr is demonstrated by monitoring the change in Fermi level under illumination for conventional PbS‐QD/Gr and for ZnO intermediate PbS‐QD/ZnO/Gr devices. These results improve the capabilities of hybrid QD/Gr configurations for optoelectronic devices. Abstract : ZnO is used as an intermediate layer in hybrid graphene/quantum dot (QD) photodetectors. ZnO forms a p–n junction to create a strong charge separation driving force to transfer electrons from the QDs to graphene. Typically, photoholes are transferred from QDs to graphene. Using a ZnO layer, photoelectrons are selectively transferred from the QDs to graphene with improved photoresponsivity.